Hubungan Tingkat Pengetahuan dan Sikap Pasien Hipertensi dalam Mengontrol Tekanan Darah di Wilayah Kerja UPTD Puskesmas Kemalaraja Tahun 2023 - Wilinda Sumantri, Apria (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Hypertension is a disease that can affect anyone, both young and old, as well as the rich and the poor. Hypertension is one of the deadliest diseases in the world. In general, the aim of the study was to find out the relationship between the level of knowledge and attitudes of hypertensive patients in controlling blood pressure in the working area of the UPTD Puskesmas Kemalaraja in 2022. This research includes research using quantitative correlation methods with a cross sectional approach and a sample size of 76 hypertension sufferers. The variables studied were presented in the form of a frequency distribution table and tested with univariate and bivariate analysis, namely by using a demographic data questionnaire, a respondent’s knowledge questionnaire in controlling blood pressure, a respondent’s attitude questionnaire in controlling blood pressure and a questionnaire controlling blood pressure. From the results of the analysis it was found that out of 76 respondents, there were 32 (42.1%) respondents with good blood pressure control, and 44 (57.9%) respondents with poor blood pressure control. The results of the chi square test obtained a p value of 0.000, meaning that there was a significant relationship between knowledge and controlling blood pressure in the working area of the UPTD Puskesmas Kemalaraja in 2022. The results of the chi square test obtained a p value of 0.000 meaning that there was a significant relationship between attitudes and controlling blood pressure in the working area of the UPTD Kemalaraja Health Center in 2022. The conclusion in this study is that there is a relationship between the level of knowledge and attitudes of hypertensive patients in controlling blood pressure in the working area of the UPTD Puskesmas Kemalaraja in 2022